Linguistic Studies of Imam Al-Bukhari: A Descriptive and Analytical Study - Al-Kharrat, Youssef Abu-Bakr ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2015)
This study explores the linguistic insights of Imam al-Bukhari as reflected in his renowned work al-Jāmiʿ al-Ṣaḥīḥ. It highlights his strong command of the Arabic language and linguistic acumen, particularly evident in his commentaries on hadiths and narrations. Adopting a descriptive-analytical approach, the paper is structured into six key sections: evidence of al-Bukhari’s linguistic proficiency, his grammatical orientation, narrations from linguistic scholars, his lexical interpretations, his morphological and syntactic views, and his mastery in employing stylistic expressions. The study aims to shed light on al-Bukhari’s linguistic competence within his hadith scholarship. The paper concludes with a summary of findings and includes a list of consulted sources and references.